Influence of stocking density on the culture potential of endangered riverine catfish Rita rita (Hamilton, 1822) in raceway - Ali, Muhammad Forhad; Sarder, MD. Rafiqul Islam; Rahman, Mohammad Matiur; Mollah, MD. Fazlul Awal (Indian Journal of Fisheries, 2018)
Endangered catfish Rita rita were reared in a cemented raceway to observe the culture potentiality at three different stocking densities (4, 8 and 16 juveniles/m3) under the three treatments (T1, T2 and T3, respectively) with three replications each. The mean initial length and weight of Rita juveniles were 20.15±1.51 cm and 100.26±6.57 g, respectively. The fish were reared by providing clean poultry viscera (containing 48.56% crude protein) at 3% of biomass once a day. The water quality parameters were measured daily and found them within suitable ranges. The growth parameters such as final mean total length, relative length gain, mean body weight, relative weight gain, SGR and condition factor were significantly (p<0.5) higher in T1 compared to those of T2 and T3. The survival rate was 100% in all the treatments, and the fish production was significantly (p<0.5) higher in T3 (8.38±0.04 kg/m3 and 8380.40±4.05 kg/ha) than those of T2 (4.49±0.03 kg/m3 and 4493.00±3.22 kg/ha) and T1 (2.36±0.02 kg/m3 and 2362.00±2.00 kg/ha). Though the growth performance of R. rita was significantly influenced by the lowest stocking density but the production findings suggest that this species can be reared at the minimum density of 16 juveniles/m3 in cemented raceway with suitable environment and adequate supplemental feed.